Simulation of Peroxiredoxin II and Brain-type Creatine Kinase protein-protein interaction using the on-line docking server ClusPro 2.0 - Anar Rakhmetov, Sang Pil Lee, Dmytro Grebinyk, Ludmila Ostapchenko, Ho Zoon Chae (Journal of Applied Pharmaceutical Science, 2015)
Importance of dedicated web servers and specialized software for simulations of protein-protein interactions is well established. The purpose of our study was to examine the protein-protein interaction that occurred under physiological and stress conditions between peroxiredoxin II and the creatine kinase brain-type using protein-docking server ClusPro 2.0. To predict the particular site of amino acid docking, computer software analyzes various protein conformations and chooses the most profitable energy state, therefore selecting a number of possible combinations that would fit the correct profile. By co-immunoprecipitation assay, we demonstrated that two molecules Prx II and CKBB have interacted with further attenuation of this specific binding by pretreatment with selected stress factors. In previous study, we showed that the enzymatic activity of CKBB was recovered by different concentration ratios of Prx II. The specific binding models were generated by ClusPro 2.0 protein docking server and studied using PyMol software. It was shown that a number of amino acid residues including Lys 11, Arg 13, Ala 204, Arg 209for creatine kinase, and Asp 181, Glu 192, Lys 196, Glu 162, Gln 163 for Prx II have participated in the complex formation throughout the first ten conformations.
Keywords: Peroxiredoxin II, creatine kinase b-type, interaction, neurodegenerative disorders.